Mythical Images and Demystification: Salome in Hispanic Modernism (Castilla. Estudios de Literatura, 2016)
This article will focus on the analysis of the Salome myth in Hispanic Modernism through the poems of Francisco Villaespesa, Rubén Darío and Delmira Agustini. Thus, we will examine the transformation of this femme fatale, from the construction of this literary archetype to the final demystification in Agustini’s poetry. Following the intertextuality in this myth and the debts to literature and other arts of Fin de Siècle in Europe, we will study the causes and the determinant of the perverse images of Salome, both aesthetically and ideologically. Ultimately, despite all the changes and transformations, due to its essence of subversion, this myth is and always will be poetized and rewritten. In its different versions, the myth of Salome will always be an instrument which the fin-de- siècle artist use in order to produce an alternative to the utilitarian bourgeois society